Utilization of Technology to Enhance Accessibility of Public Services for the Community - Muhamad Sahlan; Ramadani Saputra (Program Pascasarjana Universitas Negeri Makassar, 2021)
The utilization of technology in public services has been identified as a potential solution to improve accessibility and efficiency of public services for the community. This study aims to explore the role of technology in enhancing the accessibility of public services for the community in Indonesia. The study employed a qualitative research approach and used semi-structured interviews as the primary data collection technique. The findings of the study suggest that the utilization of technology can improve the accessibility and efficiency of public services for the community in Indonesia. The study identified several factors that facilitate or hinder the implementation of technology in public services, including funding, infrastructure, and technical expertise. The study suggests that public sector organizations need to address these challenges and leverage the facilitators identified in this study to successfully implement technology-based public services initiatives.